Calculation of Consistent Plasma Parameters for DEMO-FNS Using Ionic Transport Equations and Simulation of the Tritium Fuel Cycle - Sergey Ananyev; Andrei Kukushkin (Applied Sciences, 2023)
Modeling the D and T fluxes in Fusion Neutron Source based on a tokamak fuel cycle systems was performed consistently with the core and divertor plasma. An indirect integration of ASTRA, SOLPS4.3, and FC-FNS codes is used. The feedback coupling is realized between the pumping and puffing systems in the form of changes in the isotopic composition of the core and edge plasma. In the ASTRA code, instead of electrons, ions were used in the particle transport equations. This allows better estimates of the flows of the D/T components of the fuel that have to be provided by the gas puffing and processing systems. The particle flows into the plasma from pellets, required to maintain the target plasma density <ne> = (6–8) × 1019 m−3 are 1022 particles/s. In the majority of the working range of parameters, additional ELM stimulation is necessary (by ~1-mm3-size pellets from the low magnetic field side) in order to maintain the controlled energy losses at the level δWELM~0.5 MJ. For the starting load of the FC and steady-state operation of the facility, up to 500 g of tritium are required taking into account the radioactive decay losses.